Representation of Women Physicians in Heart Failure Clinical Practice - Ersilia M DeFilippis; Yasbanoo Moayedi; Nosheen Reza (Cardiac Failure Review)
Women have been integral in the development of advanced heart failure (HF) and transplantation as a clinical subspecialty of cardiovascular medicine. However, women remain underrepresented in leadership positions, senior academic ranks and as researchers in HF. In recent years, there have been accelerating efforts to examine sex differences in the clinical and research domains of HF. The purpose of this review is to discuss the representation of women in HF training programmes and clinical practice, the demographics of HF clinicians compared with other cardiology subspecialties, the persistent sex disparities in HF practice and research environments and potential strategies to promote equity and inclusion for women in the field.